Лето - это маленькая жизнь - Митяев Олег Григорьевич (Золотая коллекция поэзии, 2021)
Экземпляры: с/ф № 8 (20220617) / Инвентарный номер: 50027 / Цена: / Авт.знак: М 67 / ГРНТИ: 17.82.10 / ББК: 84(2=411.2)6-5